More better deals - Lansdale, Joe R., 1951- (Mulholland Books, Little, Brown and Company, 2020)
Dispatched to repossess a Cadillac from a deadbeat pet-cemetery owner and his beautiful wife, an unscrupulous used-car salesman embarks on an affair that tests the limits of his character.